Migréna a hormonální antikoncepce - Niedermayerová, Ingrid (Neurologie pro praxi, 2023)
The use of hormonal contraception (HC) has been increasing in recent decades. In women with migraine, the use of HC can significantly positively as well as negatively affect the course of the disease. In women with vascular risks, the use of inappropriate HC can make them more likely to develop ischaemic stroke. In migraine without aura, it is possible to prescribe both combined and gestagen-only HC; in migraine with aura, it is the gestagen-only type only. In menstrual migraine, in order to reduce menstruation-related migraine attacks, extended-cycle or continuous-cycle combined oral contraceptives (COCs), or gestagen-only HC can be administered. COCs are contraindicated in women with a risk of ischaemic stroke and in those with a history of ischaemic stroke. In women with risk factors of ischaemic stroke, but with no history of ischaemic stroke, it is possible to administer gestagen-only HC, with this type being relatively contraindicated after having ischaemic stroke.
Keywords: ischemická cévní mozková příhoda; Risk; kontraceptiva hormonální; migréna; lidé; Contraceptives, Oral, Combined; pohlavní hormony; Migraine Disorders; riziko; Contraceptive Agents, Hormonal; klinické rozhodování; Gonadal Hormones; Humans; Ischemic Stroke; kontraceptiva orální kombinovaná; Clinical Decision-Making; ženské pohlaví; Female